Educating surgical oncology providers on perioperative opioid use: A departmental survey 1 year after the intervention. Issue 3 (23rd May 2020) - Kim, Bradford J.; Lillemoe, Heather A.; Newhook, Timothy E.; Dewhurst, Whitney L.; Arvide, Elsa M.; Katz, Matthew H. G.; Aloia, Thomas A.; Vauthey, Jean‐Nicolas; Lee, Jeffrey E.; Tzeng, Ching‐Wei D.
Abstract: Background and Objectives: A department‐wide opioid reduction education program resulted in a 1‐month change in perceptions of opioid needs and prescribing recommendations for surgical oncology patients. This study's aim was to re‐evaluate if early trends were retained 1 year later. Methods: Surgical Oncology attendings, fellows, and advanced practice providers at a Comprehensive Cancer Center were surveyed 1‐year after an August 2018 opioid reduction education program, to compare departmental and individual opioid prescribing habits. Results: The September 2019 response rate was 54/93 (58%), with 41 completing both the post‐education and 1‐year follow‐up surveys. The departmental and matched cohort continued to recommend a lower quantity of discharge opioids for all five index operations (by >50%) and expected less postoperative days to zero opioid needs, when compared to pre‐education perceptions. Providers continued to agree that discharge opioid prescriptions should be based on a patient's last 24 hours of inpatient opioid use. There was universal agreement that each respondent's opioid administration had decreased in the past year. Conclusions: The initial 1‐month improvements in perioperative opioid prescribing perceptions were retained 1 year later by Surgical Oncology providers who recommended fewer discharge opioids, faster weaning to zero opioids, and standardized patient‐specific discharge opioid volume calculations.